1985
DOI: 10.1111/j.1474-8673.1985.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Sympathectomy on Dopamine and Noradrenaline Content of the Dog Gastrointestinal Tract*

Abstract: The content of dopamine and noradrenaline in the mucosa-submucosa and muscular layers of different gastrointestinal areas of the dog, and its modification by 6-hydroxydopamine or pargyline plus 6-hydroxydopamine was studied by means of high pressure liquid chromatography with electrochemical detection. The amounts of dopamine and noradrenaline show a cephalocaudal increase but their physiological levels were rather low when compared with those reported in other tissues. This finding was consistent with the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…This is further supported by the finding that a considerable amount of Aaad, at least that present in the jejunum, is located in the sparsely innervated mucosa. Another result favouring the view that a considerable amount of the dopamine in the intestinal mucosa is non-neuronal in location is that denervation by 6-hydroxydopamine increases the proportion of dopamine to noradrenaline (Esplugues et al, 1985;Graffner et "1, 1985;Eaker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the finding that a considerable amount of Aaad, at least that present in the jejunum, is located in the sparsely innervated mucosa. Another result favouring the view that a considerable amount of the dopamine in the intestinal mucosa is non-neuronal in location is that denervation by 6-hydroxydopamine increases the proportion of dopamine to noradrenaline (Esplugues et al, 1985;Graffner et "1, 1985;Eaker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…There are dopamine-containing enterochromaffin cells in the mucosa/submucosa of several regions of the stomach and small intestine (164). Significant and detectable quantities of l -DOPA produced by non-neuronal cells that express tyrosine hydroxylase in mesenteric organs (gastrointestinal tract, spleen, and pancreas) are released into the circulation (154).…”
Section: Structure and Function Of The Renal Dopaminergic Systemmentioning
confidence: 99%
“…The current view of the intestinal dopaminergic system is that of a local non‐neuronal system constituted by epithelial cells of intestinal mucosa, rich in aromatic L‐amino acid decarboxylase (AADC) activity and using circulating or luminal 3,4‐dihydroxyphenylalanine (L‐DOPA) as a source for dopamine (Vieira‐Coelho et al ., 1997). Dopamine is particularly abundant in the mucosal cell layer (Eaker et al ., 1988; Esplugues et al ., 1985). Studies on the formation of dopamine from exogenous L‐DOPA along the rat digestive tract showed that the highest AADC activity is located in the jejunum (Vieira‐Coelho & Soares‐da‐Silva, 1993).…”
Section: Introductionmentioning
confidence: 99%